Implementasi Penilaian Portofolio dan Unjuk Kerja dalam Mengukur Kemampuan Berpikir Kritis Matematis Siswa SMP Negeri 4 Banyumas - Uswatun Khasanah; Nasywa Alya Syafitri; Arif Wisnuadi Erhatmono; Ignasia Imannurzaky Ozora; Kusno (Griya Journal of Mathematics Education and Application, 2026)
Critical thinking skills in mathematics are among the essential competencies that need to be developed in junior high school mathematics education. However, assessment practices in mathematics learning still tend to emphasize final outcomes through written examinations, resulting in limited evaluation of students' thinking processes. This study aims to describe the implementation of portfolio assessment and performance assessment in evaluating students' mathematical critical thinking skills at SMP Negeri 4 Banyumas. The study employed a qualitative approach using a descriptive research method. Data were collected through interviews with mathematics teachers and documentation of students' work. Data analysis was conducted descriptively through the stages of data reduction, data display, and conclusion drawing. The findings revealed that performance assessment was implemented through group presentations, classroom problem-solving activities, and final quizzes, while portfolio assessment was conducted through individual assignments and students' work collected throughout the learning process. Both assessment types provided more comprehensive insights into students' mathematical critical thinking skills compared to traditional assessment methods. The study indicates that authentic assessment can support teachers in evaluating students' thinking processes, engagement, and mathematical communication skills more thoroughly.